Involvement of MIR-126 and MMP9 in the Pathogenesis of Intra-Abdominal Fistulizing Crohn’s Disease: A Brief Research Report - Luceri, Cristina; D’Ambrosio, Mario; Bigagli, Elisabetta; Cinci, Lorenzo; Russo, Edda; Staderini, Fabio; Cricchio, Marta; Giudici, Francesco; Scaringi, Stefano (Frontiers in Surgery, 2022)
Background: Intra-abdominal fistulas are complications that affect a significant proportion of Crohn’s disease patients, often requiring surgery. The aim of the present work was to correlate the occurrence of intestinal fistulization to the clinico-pathological features of these patients and to the plasma levels of MMP9, a gelatinase involved in the pathophysiology of fistula formation, and of miR-126, appearing to modulate MMP9 expression. Methods: In a series of 31 consecutive Crohn’s patients admitted to surgery due to therapeutic failure and/or complicated disease, we identified nine cases of abdominal fistulas, mainly entero-enteric fistulas. MMP9 protein was determined in plasma and at the intestinal level using immunometric assays. Circulating miR-126 was also measured in all plasma samples by real-time PCR. Results: Comparing patients with and without intra-abdominal fistulas, we did not observe differences in terms of age, gender, disease location and duration, number of previous surgeries and pre-biologic medications. However, cases with intra-abdominal fistulas had a significantly higher CDAI (p<0.0001) and a significantly lower circulating miR-126 (p<0.05). Patients with intra-abdominal fistulas had also a significantly higher amount of circulating MMP9 (p<0.0001) and this data was correlated with an increased expression of MMP9 protein in the mucosa and with reduced levels of circulating miR-126. Receiver operating characteristic (ROC) analysis pointed out the ability of circulating MMP9 to discriminate patients with and without intra-abdominal fistulas. Conclusions: These data confirm that circulating MMP9 can be used for the identification of cases with intra-abdominal fistulas and suggest that miR-126 may be also involved in the pathogenesis of this complication and that it may be further investigated as a new therapeutic strategy or for monitoring therapeutic response in these patients.